Synthesis of Uniform Gold Nanorods with Large Width to Realize Ultralow SERS Detection. Issue 27 (14th April 2021) - He, Hongpeng; Wu, Chenshuo; Bi, Cuixia; Song, Yahui; Wang, Dayang; Xia, Haibing
Abstract: In this work, we successfully demonstrate high‐yield synthesis of high‐quality gold nanorods (Au NRs) with width ranging from 6.5 nm to 175 nm by introducing heptanol molecules as secondary templating agents during cetyltrimethylammonium bromide‐templated, seeded growth method. The results show that an appropriate concentration of heptanol molecules not only alter the micellization behavior of CTAB in water, but also help silver ions impact the symmetry‐breaking efficiency of additional Au−NP seeds in addition to enhancing the utilization of gold precursors. Moreover, the generality and versatility of the present strategy for synthesis of Au NRs with flexible controlled dimensions are further demonstrated by successful synthesis of Au NRs with the assistance of other fatty alcohols with properly long alkyl chains. Furthermore, when arrays of vertically aligned Au NRs with large width (AVA−Au120×90 NRs) are used as SERS substrates, they can achieve the ultralow limit of detection for crystal violet (10 −16  M) with good reliability and reproducibility, and the rapid detection and identification of residual harmful substances. Abstract : High‐quality gold nanorods (Au NRs) with width ranging from 6.5 nm to 175 nm were successfully synthesized by introducing heptanol molecules during cetyltrimethylammonium bromide‐templated, seeded growth method. The array of vertically aligned Au NRs as SERS substrates can achieve the ultralow limit of detection (LOD) (10 −16  M for CV probes) with good reliability and reproducibility. Thanks to their LOD, they can be used for rapid detection and identification of residual harmful substances with an ultralow concentration.